1995
DOI: 10.1093/jn/125.7.1854
|View full text |Cite
|
Sign up to set email alerts
|

Skin Lycopene Is Destroyed Preferentially over β-Carotene during Ultraviolet Irradiation in Humans

Abstract: This placebo-controlled study examined in healthy women the effects of ingestion of a single large dose of beta-carotene (120 mg) on the concentrations of beta-carotene and lycopene in plasma and skin, and the effects of UV light exposure on the concentrations of beta-carotene and lycopene in the skin. Ingestion of beta-carotene increased plasma beta-carotene concentration by 127%, from 0.26 +/- 0.06 (mean +/- SEM) to 0.59 +/- 0.07 mumol/L after 1 d, and the level remained elevated at 0.54 +/- 0.11 mumol/L aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
84
1
2

Year Published

1999
1999
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 180 publications
(89 citation statements)
references
References 32 publications
2
84
1
2
Order By: Relevance
“…The importance of ascorbic acid and ␣-tocopherol was suggested by decreases of these antioxidants in skin levels with concomitant formation of lipid hydroperoxides during UV irradiation of murine skin, and the formation of squalene hydroperoxides in human skin upon UV exposure, respectively (Yamamoto, 2001). Carotenoids such as lycopene and ␤-carotene also attenuated the disorders elicited by UV irradiation (Ribaya-Mercado et al, 1995;Stahl et al, 2001). Although feeding red bell pepper attenuated the increase in the grading score in SAMP8 in our previous study, supplementation with lycopene or tomato could not do.…”
Section: Discussioncontrasting
confidence: 54%
“…The importance of ascorbic acid and ␣-tocopherol was suggested by decreases of these antioxidants in skin levels with concomitant formation of lipid hydroperoxides during UV irradiation of murine skin, and the formation of squalene hydroperoxides in human skin upon UV exposure, respectively (Yamamoto, 2001). Carotenoids such as lycopene and ␤-carotene also attenuated the disorders elicited by UV irradiation (Ribaya-Mercado et al, 1995;Stahl et al, 2001). Although feeding red bell pepper attenuated the increase in the grading score in SAMP8 in our previous study, supplementation with lycopene or tomato could not do.…”
Section: Discussioncontrasting
confidence: 54%
“…Although nutrients were not measured in the skin itself, previous studies showed that the profiles of carotenoids, ␣-tocopherol, and retinoids in blood and skin are comparable (26,27). Moreover, many vitamins have been shown in the skin and in skin-surface lipids derived from sebum and corneocytes, including vitamin A, ␣-and ␤-carotene, lycopene, lutein, zeaxanthin, and ␤-cryptoxanthin (28)(29)(30).…”
Section: Discussionmentioning
confidence: 99%
“…It has also been shown that ␤-carotene and lycopene are effective protectors of lymphocyte cells from nitrogen dioxide radical damage, but lycopene is at least twice as effective as ␤-carotene (6). RibayaMercado et al (7) showed that when skin is subjected to ultraviolet light stress, more lycopene is destroyed than ␤-carotene, suggesting a role of lycopene in mitigating oxidative damage in tissues.…”
Section: Introductionmentioning
confidence: 99%